Mitigating the risks of post-acute sequelae of SARS-CoV-2 infection (PASC) with intranasal chlorpheniramine: perspectives from the ACCROS studies - Fernando Valerio-Pascua; Fernando Baires; Anupamjeet Kaur Sekhon; Mari L. Tesch; Estela Jackeline Pineda; Syed A. A. Rizvi; Jarmanjeet Singh; David Abraham Cortes-Bandy; Amy C. Madril; Jana Radwanski; Anita S. Lewis; Miguel Sierra-Hoffman; et al. (BMC Infectious Diseases)
Abstract Background The World Health Organization (WHO) declared the end of the COVID-19 (SARS-CoV-2) global public health emergency on May 5, 2023, but its long-term consequences have still been haunting the global population. Post-acute sequelae of COVID-19 (PASC) and long-term COVID-19 are serious concerns and present with various symptoms. Intranasal chlorpheniramine (iCPM) has been shown to decrease the viral burden of SARS-COV-2. iCPM uses decreased COVID-19 disease progression and severity in Accelerating COVID-19 Clinical Recovery in an Outpatient Setting (ACROSS)-I & III randomized control trials (RCT). Methods This prospective survey study included 259 participants in ACROSS I and III RCTs. We compared the effect of iCPM versus placebo on the reduction of PASC symptoms. A PASC questionnaire containing 17 questions regarding the most common PASC symptoms was used in this study. T-test and Pearson chi-square statistics were performed according to continuous and categorical data using STATA 17.0 Basic Edition software. Findings The iCPM cohort had a lower proportion of patients with fatigue or tiredness vs. placebo (0 Vs 17, 21, p < 0.001). iCPM cohort had a lower proportion of patients with difficulty concentrating or mental confusion (0 vs. 22, 27, p < 0.001). iCPM cohort had also a lower number of patients with difficulty in the ability to perform daily activities or work vs. placebo (1 Vs 38, 48, p < 0.001). A smaller number of patients in the iCPM cohort sought medical attention for PACS symptoms compared to placebo (0 vs. 48, 68, p < 0.001). Interpretation The use of intranasal chlorpheniramine shows promise in preventing COVID-19 progression to the often-debilitating post-COVID-19 syndrome PASC. The association between iCPM use and a lower prevalence of PASC symptoms is strong. Further studies are needed to establish the role of ICPM in preventing PASC.